1994
DOI: 10.1177/08959374940080021601
|View full text |Cite
|
Sign up to set email alerts
|

Caries-Protective Factors in Saliva

Abstract: Saliva influences caries attack mainly by its rate of flow and by its content of fluoride. The salivary flow rate influences to a high degree the rate of oral and salivary clearance of bacterial substrates included in foods and snacks. This influence is site-dependent. The basal salivary fluoride concentration is low, about 1 mumol/L, independent of salivary flow rate, and not influenced by diurnal variation. After an exposure of the oral cavity to fluoride, the increased fluoride level is decreased by a proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
14

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 143 publications
(106 reference statements)
4
59
0
14
Order By: Relevance
“…[6] The mean or average pH of normal resting saliva is 6.75, which shows that normal resting saliva is slightly acidic. [5,7] Hawkins [8] reported that there was a higher pH in saliva of persons who are immune from caries than in those who are susceptible. This was confirmed by reports from both Vitorino et al [9] and Zhou et al [10] showing that a higher pH in saliva of persons who are immune from caries than in those who are susceptible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] The mean or average pH of normal resting saliva is 6.75, which shows that normal resting saliva is slightly acidic. [5,7] Hawkins [8] reported that there was a higher pH in saliva of persons who are immune from caries than in those who are susceptible. This was confirmed by reports from both Vitorino et al [9] and Zhou et al [10] showing that a higher pH in saliva of persons who are immune from caries than in those who are susceptible.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The major regulator of pH is salivary bicarbonate from parotid saliva. [6] The mean or average pH of normal resting saliva is 6.75, which shows that normal resting saliva is slightly acidic.…”
Section: Introductionmentioning
confidence: 99%
“…Se comportan como electrolitos, los más importantes son: sodio, potasio, cloruro y bicarbonato; estos contribuyen con la osmolaridad de la saliva, la cual es la mitad de la del plasma, por lo tanto, la saliva es hipotónica con respecto al plasma. 9,12 La concentración de los componentes orgánicos e inorgánicos disueltos presenta variaciones en cada individuo según las circunstancias como el flujo salival, el aporte de cada glándula salival, el ritmo circadiano, la dieta, la duración y naturaleza del estímulo, 1,9,13 las cuales generan diferentes funciones dentro de nuestra cavidad oral, se mantiene una flora bacteriana controlada y un pH estable. 14 …”
Section: Componentes Inorgánicosunclassified
“…Dentre as muitas propriedades inerentes ao fluido salivar encontram-se: um sistema tampão com capacidade neutralizadora dos áci-dos 30,31,33 ; funções remineralizadoras 30,31,34 e de retardo da desmineralização do esmalte 30,32,33 .…”
Section: H I P O F U N ç ã O D a S G L â D U L A S S A L I V A R E Sunclassified
“…Ademais, seus fatores antimicrobianos constituem a primeira linha de defesa da cavidade oral [30][31][32][33][34] ; presentes na placa bacteriana 30,32 e na película dental, conferindo proteção contra agressões químicas e físicas 30,31,33 . A hipofunção das glândulas salivares pode ser definida pela redução do fluxo salivar, da capacidade tampão e dos constituintes salivares, principalmente as proteínas 35 , o que predispõe a uma maior prevalência de cárie dentária.…”
Section: H I P O F U N ç ã O D a S G L â D U L A S S A L I V A R E Sunclassified